1983
DOI: 10.1037/0096-1523.9.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for scale structure in melodic sequences.

Abstract: Most Western music is tonal; that is, pitch organization can largely be described in terms of scales or keys. A considerable amount of research has been conducted on the role played by scale in perceiving notes and melodies. The present article points out a potentially important distinction between scale structure (the set permitted pitch intervals between notes) and mode (the assignment of a special salience or centrality to particular notes within the scale structure). Four experiments are described that inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Contrary to some aesthetic theories that predict maximum preference for musical excerpts that depart from typicality (e.g. Meyer, 1956), both Cross et al (1983) and Smith and Melara (1990) have shown that nonmusicians as well as musicians prefer musical sequences that are most typical of the tonal idiom. This finding is consistent with another current of experimental research showing that more familiar stimuli are consistently preferred (e.g.…”
Section: Experiments 6: Tonal Preference and Advantagesmentioning
confidence: 81%
See 1 more Smart Citation
“…Contrary to some aesthetic theories that predict maximum preference for musical excerpts that depart from typicality (e.g. Meyer, 1956), both Cross et al (1983) and Smith and Melara (1990) have shown that nonmusicians as well as musicians prefer musical sequences that are most typical of the tonal idiom. This finding is consistent with another current of experimental research showing that more familiar stimuli are consistently preferred (e.g.…”
Section: Experiments 6: Tonal Preference and Advantagesmentioning
confidence: 81%
“…Tonal structure also affects musical preferences. Western listeners have an aesthetic bias for tonal sequences; they prefer melodies that are most constrained in terms of tonal rules (Cross, Howell, & West, 1983;Smith & Melara, 1990). Finally, sensitivity to specific aspects of the tonal structure is reflected in the subjects' ability to identify particular elements within the scale as being most central, like the tonic and the fifth, via the judgments of good completion of melodic patterns (Cuddy & Badertscher, 1987;Janata & Reisberg, 1988).…”
Section: Cognitive Studies Of Tonal Knowledgementioning
confidence: 98%
“…It may be the case that the unfamiliar melodies that we selected on the basis oftheir relative obscurity remained such because they are structurally poorer than the familiar melodies.> Accordingly, the overall preference for familiar melodies may be related to their greater musicality. For instance, it has been shown that Western listeners prefer musical stimuli that are most typical in terms of the tonal structure of their musical idiom (Cross, Howell, & West, 1983;Smith & Melara, 1990). Teasing apart the contribution of familiarity from musicality on liking judgments should be the goal of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A second possible cue underlying the song illusion is musical scale structure, as naïve listeners prefer musical tone sequences which conform to scale structure to tone sequences that do not (Cross et al, 1983). Moreover, listeners are better at detecting pitch changes within song illusion stimuli when they are perceived as sung than when they are perceived as spoken, but only when those changes would violate Western musical scale structure (Vanden Bosch der Nederlanden, Hannon, & Snyder, 2015b).…”
Section: Introductionmentioning
confidence: 99%